SANKSI BAGI ANAK PERILAKU KRIMINAL KASUS PENCURIAN PERSPEKTIF JINAYAH ISLAM (Studi Kasus Kota Medan): Studi Kasus di Kota Medan - Yudanata, Agung; Romadhona, Suci (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2026)
This study aims to analyze sanctions imposed on juvenile offenders in theft cases from the perspective of Islamic criminal law (jinayah), with a case study in Medan City. The increasing involvement of children in theft offenses reflects complex social problems, including economic hardship, negative peer influence, and weak parental supervision. This research employs a qualitative method with a descriptive-analytical approach. Data were collected through library research and fieldwork, including interviews with officers of the Women and Children Protection Unit (PPA) of the Medan Police, officials of the Probation Office (Bapas), the Special Child Development Institution (LPKA), and several juvenile offenders. The findings indicate that, normatively Islamic criminal law does not impose punishment on children due to the absence of full legal responsibility (taklīf); instead, juvenile offenders are subject to ta'zīr sanctions, which emphasize education, moral guidance, and rehabilitation. Empirical findings further reveal that imprisonment is relatively ineffective in preventing recidivism, while restorative and family-based approaches are more constructive and sustainable. Therefore, the resolution of juvenile theft cases within the framework of jinayah prioritizes public welfare (maṣlaḥah), rehabilitation, and the protection of the child's future. An educative-restorative ta'zīr model is proposed as a more humane alternative, consistent with the objectives of Islamic law (maqāṣid al-sharīʿah) and modern juvenile justice systems.